Interstitial Lung Diseases - Mueller-Mang, Christina (Multislice CT, 2017)
The term interstitial lung diseases (ILD) comprises a diverse group of diseases that lead to inflammation and fibrosis of the alveoli, distal airways, and septal interstitium of the lungs. The ILD consist of disorders of known cause (e.g., collagen vascular diseases, drug-related diseases) as well as disorders of unknown etiology. The latter include idiopathic interstitial pneumonias (IIPs), and a group of miscellaneous, rare, but nonetheless interesting, diseases. In patients with ILD, MDCT enriches the diagnostic armamentarium by allowing volumetric high-resolution scanning, i.e., continuous data acquisition with thin collimation and a high spatial frequency reconstruction algorithm. CT is a key method in the identification and management of patients with ILD. It not only improves the detection and characterization of parenchymal abnormalities, but also increases the accuracy of diagnosis. The spectrum of morphologic characteristics that are indicative of interstitial lung disease is relatively limited and includes the linear and reticular pattern, the nodular pattern, the increased attenuation pattern (such as ground-glass opacities and consolidation), and the low attenuation pattern (such as emphysema and cystic lung diseases). In the correct clinical context, some patterns or combination of patterns, together with the anatomic distribution of the abnormality, i.e., from the lung apex to the base, or peripheral subpleural versus central bronchovascular, can lead the interpreter to a specific diagnosis. However, due to an overlap of the CT morphology between the various entities, the final diagnosis of many ILD requires close cooperation between clinicians and radiologists and complementary lung biopsy is recommended in many cases.